Quantitative Analysis of the Effect of Marketing Networks in Increasing Sales and Market Share in Indonesia Case Study on the E-commerce Industry - Eri Mardiani; Eva Yuniarti Utami; A Idun Suwarna; Arizal Hamizar; Jacsy Tubalawony (North Press, 2024)
This research investigates the intricate dynamics between marketing network strategies, sales performance, and market share in the Indonesian e-commerce industry. Employing a quantitative research design, the study integrates descriptive statistics, correlation analysis, and multiple regression analysis to discern the impact of social media marketing, influencer collaborations, affiliate marketing, and traditional advertising. The findings, based on survey data collected from consumers and e-commerce businesses, reveal influencer collaborations as a pivotal driver, with social media marketing and affiliate marketing playing complementary roles. Traditional advertising faces challenges in the contemporary landscape. These insights offer actionable guidance for businesses seeking to optimize their marketing strategies in the rapidly evolving Indonesian e-commerce ecosystem.